Analysis of project-based science E-module development integrated with mangrove ecotourism for scientific creativity and environmental literacy - Sucilestari, Ramdhani; Ramdani, Agus; Susilawati, Susilawati; Sukarso, AA; Rokhmat, Joni (Edelweiss Applied Science and Technology, 2025)
Developing project-based e-modules integrated with mangrove ecotourism is essential for fostering students’ scientific creativity, particularly within the context of learning in the digital era. This study aims to examine student perceptions of project-based science e-modules integrated with ecotourism and their impact on scientific creativity and environmental literacy. Data were collected through an online Likert scale questionnaire administered to 409 students from eight universities across Indonesia. The data analysis employed a descriptive quantitative approach followed by path analysis. The results revealed that most respondents held a positive perception of the project-based e-module. Most participants agreed that the e-module effectively enhances scientific skills and environmental literacy while promoting critical thinking on environmental issues. Additionally, the e-module was perceived to provide relevant examples of local environmental conditions and to raise awareness about individual contributions to environmental conservation. These findings suggest that ecotourism-integrated project-based e-modules have significant potential to improve students’ scientific creativity and environmental literacy. By integrating real-world environmental issues, this e-module enriches students’ understanding of the interplay between science and environmental conservation, encouraging greater engagement with environmental sustainability. This research offers valuable insights into the development of contextualized and practical learning approaches in science education.